Impact of socioeconomic status on coronary mortality in people with symptoms, electrocardiographic abnormalities, both or neither: the original Whitehall study 25 year follow up. Issue 7 (1st July 2000) - Hemingway, Harry; Shipley, Martin; Macfarlane, Peter; Marmot, Michael
Abstract : OBJECTIVES: To determine the impact of socioeconomic status (SES) on coronary heart disease (CHD) mortality in people with and without prevalent CHD at baseline. DESIGN: Cohort study with 25 year follow up; prevalent CHD was defined by Q, ST or T wave electrocardiographic (ECG) abnormalities or symptoms (defined by the Rose chest pain questionnaire and self reported doctor diagnosis) or both. SES was defined by four civil service employment grades. SETTING: London. PARTICIPANTS: 17 907 male civil servants aged 40–69 years. MAIN OUTCOME MEASURES: CHD mortality (n=2695 deaths). RESULTS: The lowest versus highest employment grade was associated with increased CHD mortality (age adjusted hazard ratio 1.56 (95% CI 1.2, 2.1)), prevalence of symptoms and, among symptomatic participants only, the prevalence of Q, ST or T abnormalities. Thirty one per cent of CHD deaths occurred in participants with prevalent CHD at baseline. Among participants without Q, ST or T abnormality employment grade was associated with CHD mortality; the hazard ratios (lowest v highest grade) adjusted for age, systolic and diastolic blood pressure were 1.72 (95% CI 1.4, 2.1) for asymptomatic and 1.52 (95% CI 1.1, 2.1) for symptomatic participants; among participants with Q, ST or T abnormality the corresponding hazard ratios were 1.46 (95% CI 0.7, 2.9) and 1.14 (95% CI 0.6, 2.0) respectively. CONCLUSIONS: SES was inversely associated with CHD mortality in civil servants with and without prevalent CHD at baseline. Further distinguishing the relative contribution of SES to the initiation and progression of CHD requires repeated measures studies of pre-clinical and clinical measures of CHD.